MANAJEMEN KOMUNIKASI KRISIS INSTANSI PEMERINTAH DALAM MENGHADAPI SPEKULASI PASAR DAN FLUKTUASI EKONOMI - Usi Falira Rohaina; Syaiba Safira; Serlia Risky Alina; Sultan Badaruddin; Sri Hertimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
Dynamic global economic fluctuations are often exacerbated by market speculation and information distortion in the public sphere. This study aims to analyze the crisis communication management strategy of government agencies in dealing with market speculation and maintaining national economic stability. Using a descriptive qualitative method with a case study approach, data were gathered through in-depth interviews with public relations practitioners from economic ministries/institutions, documentation of press releases, and digital footprint analysis on social media. The results indicate that successful economic crisis management relies on three main strategies: implementing an AI-driven media monitoring system as an early warning instrument for market sentiment; enforcing a single source of truth policy to eliminate sectoral egos and information misalignment between agencies; and simplifying complex macroeconomic narratives into down-to-earth visual content for the general public. This study concludes that tactical, data-driven communication synchronization not only mitigates psychological market panic instantly but is also crucial in maintaining public trust and a stable investment climate.